2020
DOI: 10.1109/jstars.2019.2950466
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Plastic Greenhouses Using Spectral Metrics Derived From GaoFen-2 Satellite Data

Abstract: Plastic greenhouses are an important hallmark of agricultural progress. To meet the growing demand for vegetable and food, the amount of plastic greenhouses has increased significantly over the past few decades. Remote sensing is considered as a promising data source for taking inventory and monitoring plastic greenhouses for managing modern agriculture. However, a systematic catalog of number and spatial distribution of plastic greenhouses is mostly inexistent. This is primarily due to the complex land surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…where is the sigmoid activate function and [, ] denotes to concatenate two tensors. 1 is a weight matrix to be learned and 47+ is previous hidden state which has the same dimension compared with input 4 . In a similar way, the update gate is computed by…”
Section: R-cnn Does To Obtain Features Of Images In the Beginningmentioning
confidence: 99%
See 1 more Smart Citation
“…where is the sigmoid activate function and [, ] denotes to concatenate two tensors. 1 is a weight matrix to be learned and 47+ is previous hidden state which has the same dimension compared with input 4 . In a similar way, the update gate is computed by…”
Section: R-cnn Does To Obtain Features Of Images In the Beginningmentioning
confidence: 99%
“…HANKS to the development recently in computer vision, the past few decades have seen the rapid progress in remote sensing technology which has brought quantities of applications [1]- [4], such as environmental management, forecasts of disasters, and assistance in rescue operations. Development of VHR (very high resolution) remote sensing images provide us with more detailed geo-spatial objects information including diversities in scale, orientation, and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [10] reported that, when using a single-texture algorithm to identify plastic greenhouses, the recognition accuracy of a local binary model exceeds that of the gray-level co-incidence matrix and the pixel shape index algorithm. Shi et al [13] proposed a three-step stratified model to extract plastic greenhouses based on GF-2 remote-sensing data; that is, they first distinguished plastic greenhouses, vegetation, and other feature types by using the double-coefficient vegetation screening index. Next, they used the high-density vegetation suppression index to screen out high-density vegetation features.…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse classification research works have been performed by using numerous pixel-based and object-based classification methods with several remote sensing data, such as Landsat Thematic Mapper [7], Landsat-8 Operational Land Imagery (OLI) [8], the Terra Advanced Spaceborne Thermal Emission and Reflection Radiometer, IKONOS, QuickBird [9], WorldView-2 (WV2) [10], [11], GaoFen-2 [12], and Sentinel-1 and Sentinel-2 MultiSpectral Instruments (MSI) [5].…”
mentioning
confidence: 99%
“…It was also stated that textural information shows a positive effect on PML classification with SVM and RF classifiers. Shi et al [12] proposed a plastic greenhouse mapping method based on the GaoFen-2 image with a three-step procedure. They reached an OA of 97.34%.…”
mentioning
confidence: 99%